Influence of cervical margin relocation (CMR) on periodontal health: 12-month results of a controlled trial. (February 2018) - Ferrari, Marco; Koken, Serhat; Grandini, Simone; Ferrari Cagidiaco, Edoardo; Joda, Tim; Discepoli, Nicola
Abstract: Objectives: The concept of Cervical Margin Relocation (CMR) consists on placing a base layer of direct resin composite to elevate supra-gingivally the proximal indirect bonded restorations. The aims of this clinical study were to evaluate 1. Bleeding on Probing (BoP) on posterior indirect restorations with one interproximal margin relocated cervically, and 2. possible correlation between depth of the interproximal margins and BoP. Methods: CMR (Group 1) and shoulder preparations (Group 2) were performed in 35 posterior teeth and evaluated after 12 months (T12). Cavities' margins were placed below the Cemento-Enamel-Junction (CEJ). CMR was applied in one interproximal box-slot preparation using G-Premio Bond, for dentin hybridization, and universal flow resin composite (GC Co. Tokyo, Japan). Pressed lithium disilicate crowns (LS2) (LiSi Press, GC Co. Tokyo, Japan) were made and placed with proprietary luting material. At baseline and after 12 months, clinical surrogate parameters were assessed; and measurements were recorded for the restorative margin position in relation to margo gingivae by probing, and radiographically, the distance from the bone crest was calculated (in mm). Statistical analysis was performed. Results: CMR was associated with statistically significant increased BoP scores compared to shoulder preparation at T12 (53.0% vs. 31.5% per site, respectively) (p = 0.10). Gingival Index (GI) and Plaque Index (PI) were not statistically different between both groups. The linear distance between the bone crest and the restorative margin was 2 mm in 13 out of 19 experimental sites of Group 1, and 6 out of 11 of Group 2. Conclusions: Higher incidence of BoP can be expected around teeth treated with the concept of CMR and in coincidence with deep margins placed at or closer than 2 mm from the bone crest. Clinical significance: CMR is a clinically sensitive-technique, especially when performed on deep subgingival margins.